Pengaruh Motivasi dan Persepsi Kualitas terhadap Keputusan Berkunjung Pada Destinasi Wisata Monumen Rawgede di Masa Pandemi Covid-19 - Megawati Dewi Yunitasari; Eman Sulaeman (J-MAS (Jurnal Manajemen dan Sains), 2022)
This research aims to determine, analyze, and explain how the partial and simultaneous influence of motivation and tourist perceptions on the decision to visit the Rawagede Monument tourist attraction during the covid-19 pandemic. This research uses quantitative research with descriptive and verification methods. The population in this study were visitors to the Rawagede Monument tourist attraction in 2022. The population in 2022 was searched using a linear trend. The sample to be tested in this study amounted to 390 people with sampling using slovin. This study uses a non-probability sampling technique with a purposive technique. The data analysis technique uses scale range analysis and path analysis with the SPSS 21 software analysis tool for windows.Based on the results of research that has been done, it shows that the motivation to get an average score of 1.431 is in the good criteria, the perception of getting an average score of 1.282 is in the pretty good criteria, the decision to visit gets an average score of 1.445 is in the good criteria. The correlation coefficient between motivation and perception variables is 0.535, the correlation level is moderate, quite strong. The partial effect of motivation on the decision to visit is 10.1% while the perception of the decision to visit has a larger contribution of 10.4%, simultaneously the total influence of motivation and perception on the decision to visit is 31.6% while the remaining 68.4% is another influence not measured in this study.